A Stitch in Time? Mutual Trust as the EU’s Fix-All in Case C-183/23 Commission v Malta - Ruairi O'Neill (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 463-487 | Article | (Table of Contents) 1. Introduction. – 2. The (limited) substance of the judgment in Commission v Malta: what it says about citizenship per se. – 3. The concrete expression of solidarity. – 4. EU citizenship is based on mutual trust. – 4.1. How has mutual trust been applied in the internal market already? – 4.2. How could mutual trust impact upon Union citizenship? – 5. The practical outcome of the judgment: legal certainty and existing beneficiaries. – 6. The wider influence of Article 2 TEU on the EU legal order. – 7. The continuation of an emerging pattern. – 8. Conclusion. | (Abstract) In Case C-183/23, the Court of Justice of the European Union ruled on the legality of Malta’s investor citizenship scheme, holding that national citizenship cannot be acquired on a purely transactional basis. Since Union citizenship is automatically conferred upon the acquisition of national citizenship, the Court anchored the former in the EU value of solidarity, effectively imposing analogous conditions on the latter. The judgment further reinforced this reasoning by invoking the principle of mutual trust, which serves as the constitutional foundation for the cross-border recognition of national citizenship and the derived rights of Union citizenship. This landmark ruling is significant for two key reasons: first, it explicitly links Union citizenship to mutual trust, and second, it frames the free movement of Union citizens as a concrete expression of the values enshrined in Article 2 TEU. However, uncertainties remain regarding the judgment’s future implications – particularly whether Member States may refuse to recognise Union citizenship status and its derived rights, or whether more generally the disapplication of a measure based on mutual trust could simultaneously protect an EU value while infringing individual rights. This would be an exceptional, and therefore extremely unlikely, outcome, which raises questions about the reliance on mutual trust (dealing with the effects of citizenship acquisition in other Member States) in an infringement action against a Member State concerning an administrative mechanism for the award of national citizenship in that Member State (dealing with the citizenship status itself).